Formulation and Activity Testing of Sunscreen Nanoemulsion Cream Derived from 96% Ethanol Extract of Kersen Leaves (Muntingia Calabura L.) - Rakhmi Hidayati; Sefi Ela Sari; Yulia Pratiwi; Dessy Erliani Mugita Sari (Universitas Ngudi Waluyo, 2025)
Kersen leaves contain secondary metabolite compounds, including flavonoids, phenolics, saponins, and tannins. Nanoemulsion has a colloidal dispersion that has a particle size between 10 and 200 nm. Nanoemulsion was incorporated into a cream base so that when used topically with a relatively small particle size, it can increase the penetration of active substances into the skin. This study aims to determine the physical characteristics and potential of 96% ethanol extract of kersenleaves as a sunscreen based on SPF value. This research is an experimental quantitative research which includes phytochemical screening, making nanoemulsion cream with concentrations of 2%, 4%, and 6%., testing the characteristics of the preparations, testing sunscreen activity in vitro using a UV-Vis spectrophotometer, and statistical data analysis with the SPSS program. The results of phytochemical screening of 96% ethanol extract of kersen leaves (Muntingia calabura L.) showed that the extract positively contained flavonoids, phenolics, tannins, and saponins. The results of the nanoemulsion research particle size test obtained a value of 17.65 nm, the zeta potential test (-18.30), and the transmittance percent test (94.224), which has a clear and transparent visual. Nanemulsion cream formulation with variations in the concentration of 96% ethanol extract nanoemulsion of kersen leaves at F0 (-), F1 (2%), F2 (4%), and F3 (6%) produced has good organoleptic properties and homogeneity, viscosity ranges from 2000 to 50,000 cPs, spreadability ranges from 5 to 7 cm, adhesive power is greater than 1 second, pH preparation is in the range of 4.5 to 6.5, and it is an oil-in-water emulsion type. In the results of the sunscreen activity test, the SPF value obtained at F0 (0.72) has no potential as a sunscreen, F1 (12.15) was in the maximum protection category, F2 (17.34) was in the ultra protection category, and F3 (30.56) was in the ultra protection category. Nanemulsion cream, a 96% ethanol extract of kersenleaves, has potential as a sunscreen. The most optimal nanemulsion cream formula was at an F3 concentration of 6%, with an SPF value of 30.53, entering the ultra protection category.